VCHP-ORC power generation from low-grade industrial waste heat combined with solar water heating system: Power generation and CO2 emission in industrial estate of Thailand. Issue 1 (1st January 2017) - Sonsaree, Sorawit; Asaoka, Tatsunori; Jiajitsawat, Somchai; Aguirre, Hernan; Tanaka, Kiyoshi
Abstract: In the view of the total energy consumption by economic sectors of Thailand, it was shown that the greatest energy consumption derived from the industrial sector, where consumed both thermal energy and electrical energy for the processes. In this study, a novel concept of Organic Rankine Cycle (ORC) power generation is proposed. The power is generated from a low-grade industrial waste heat (IWH) with temperature below 70°C. The system is also combined with a solar water heating system (SWHS) and a vapor compression heat pump (VCHP) as a heating booster. A 400 kW thermal capacity VCHP, with R365mfc as the working fluid, is used to rise the heat from IWH and SWHS before supplying to a 60 kWe ORC power generator with R245fa. Three types of solar collectors were used to generate heat: flat-plate, heat pipe evacuated-tube and compound parabolic concentrator (CPC). Between 300 and 700 units of each type of the collectors were connected in parallel with F R τ α e of 0.740, 0.572, 0.718, F R U L of 3.620, 0.750, 0.974 W/m 2 -K, and gross area of 2.081, 2.369, 2.160 m 2 per unit, respectively. The system is designed to produces 10 m 3 /day of hot water at 70°C. The system is mathematically modeled and simulated to evaluate the net power output, the CO2 emission, and the levelized cost of electricity (LCOE). Six areas of industrial estate consisting of, Chiang Mai (18.80°N, 98.98°E), Bangkok (13.75°N, 100.52°E), Ratchaburi (13.54°N, 99.82°E), Songkhla (7.21°N, 100.56°E), Nakhon Ratchasima (13.75°N, 100.52°E), and Chon Buri (13.40°N, 101.00°E), that represent the north, central, west, south, north-east and east part of Thailand. Their weather data was taken for the simulations. The simulation results show that the system produces high electricity when the number of the collectors is increased. Moreover, the system located in Chiang Mai produced the highest amount of electricity with the lowest LCOE. When the temperature of low-grade IWH was around 64°C, with 700 solar collector units of each type of flat-plate, heat pipe evacuated-tube, and compound parabolic concentrator (CPC) solar collectors, the system can produce 84.4, 107.0, and 117.1 MWh/Year with LCOE of 0.35, 0.28, and 0.25 USD/kWh, respectively. In terms of the environmental impact, the system can reduce CO2 emission of 46.2, 58.6, and 64.2 Ton CO2  eq./Year, respectively. From this study, it can be concluded that the VCHP-ORC system can be integrated with the SWHS and used in industrial processes for power production as well as reduction of the energy intensity and CO2 emission of the industries.